2010
DOI: 10.1016/j.tetlet.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

An alkoxide anion-triggered tert-butyloxycarbonyl group migration. Mechanism and application

Abstract: We report a fast N→O tert-butyloxycarbonyl (Boc) migration of the imide (3R,4R)-tert-butyl 3-((6-(bis(tert-butoxycarbonyl)amino)-4-methylpyridin-2-yl)methyl)-4-hydroxypyrrolidine-1-carboxylate (2) via a base-generated alkoxide. The mechanism of the migration is intramolecular, involving an unusual nine-membered cyclic transition state. Keywords N to O migration; Boc group migration; intramolecular migration; crossover experimentIn the course of research on the development of chiral pyrrolidine-based inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…SEM‐protection, reduction with LiAlH 4 , methylation and deprotection gave rise to raputimonoindole C ( 33 ) in 64 % yield over 4 steps. Interestingly, alternative N ‐Boc or N ‐TIPS protection led to undesired protecting group migration during the methylation . The use of N ‐TBS protection and methylation with Ag 2 O in MeI at 45 °C followed by deprotection with TBAF also led to raputimonoindole C ( 33 ), albeit in lower yield (29 % over 4 steps).…”
Section: Resultsmentioning
confidence: 99%
“…SEM‐protection, reduction with LiAlH 4 , methylation and deprotection gave rise to raputimonoindole C ( 33 ) in 64 % yield over 4 steps. Interestingly, alternative N ‐Boc or N ‐TIPS protection led to undesired protecting group migration during the methylation . The use of N ‐TBS protection and methylation with Ag 2 O in MeI at 45 °C followed by deprotection with TBAF also led to raputimonoindole C ( 33 ), albeit in lower yield (29 % over 4 steps).…”
Section: Resultsmentioning
confidence: 99%
“…Di-Boc protection of 10 also was fruitless because one of the Boc groups is transferred to the oxyanion of 11 upon condensation of di-Boc- 9 with tert -butyl 6-oxa-3-azabicyclo[3.1.0]hexane-3-carboxylate, as described earlier. 10a The hydroxyl group of 11 was first protected with t -butyldimethylsilyl chloride (TBSCl) in the presence of imidazole to give the silyl ether ( 12 ) in excellent yields. Next, the NH of the carbamate group on the pyridine ring was further protected with another Boc protecting group using (Boc) 2 O in the presence of 4-dimethylaminopyridine (DMAP) to yield 13 in high yields, then the silyl ether was cleaved using tetrabutylammonium fluoride (TBAF) to provide the tri-Boc protected alcohol ( 14 ) in very high yields.…”
Section: Chemistrymentioning
confidence: 99%
“…1011 Alkene 16 was treated with ozone, followed by dimethyl sulfide to generate 17 in excellent yields. Aldehyde 17 underwent a reductive amination reaction with the corresponding amines in the presence of NaHB(OAc) 3 to give 18, 19a–e in high yields.…”
Section: Chemistrymentioning
confidence: 99%
“…Our recent study demonstrated that di-Boc deprotected 4′-[(6-aminopyridin-2-yl)methylpyrrolidin]-3′-ol ( 5b ) can cause a fast N → O Boc migration via a base-generated alkoxide. 16 The mechanism of the migration is intramolecular, implicating an unusual nine-membered cyclic transition state.…”
Section: Introductionmentioning
confidence: 99%